THE EFFECT OF ZINC OXIDE ON SOME CYTOGENETICS PARAMETERS IN WHITE MOUSE - الركابي عبد الامير (Iraqi Journal of Science, 2024)
The aim of this study wase focusing some light to detect the cytogentic effects of zinc oxide through using cytogentic analysis (Mitotic index and chromosomal aberrations on the somatic and sex cells and sperm head abnormalities) on Balb/c mice.Ninty eight male mice were used in this study, these animals were divided into two groups the first one was the controlling groups and the second one was. Treated with Zinc Oxide.The results showing that the Zinc Oxide causes an inhibition of mitotic index in somatic and sex cells and the inhibition increased by augmenting the concentration, where the effect was significant (P<0.01) , and the effect of doses were significant (P<0.05), in both kinds of cells.The chromosomal aberration increased pursuant to the raising of zinc oxide concentration.The influence was significant (P<0.01). The doses had an effect on the occurance of aberration (P<0.05) in the chromatidal breaks of sex cells only.Also Zinc Oxide had a significant influence (P<0.01) in sperm head abnormalities, while the periods did not show a significant effect. This indicated that the cells were sensitive to the material (Zno) in all the stages of spermatogenesis.